2006
DOI: 10.1002/jmri.20727
|View full text |Cite
|
Sign up to set email alerts
|

Correction of eddy‐current distortions in diffusion tensor images using the known directions and strengths of diffusion gradients

Abstract: Purpose:To correct eddy-current artifacts in diffusion tensor (DT) images without the need to obtain auxiliary scans for the sole purpose of correction. Materials and Methods:DT images are susceptible to distortions caused by eddy currents induced by large diffusion gradients. We propose a new postacquisition correction algorithm that does not require any auxiliary reference scans. It also avoids the problematic procedure of cross-correlating images with significantly different contrasts. A linear model is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 17 publications
0
101
0
Order By: Relevance
“…It is unclear how this may have affected our study findings; however, no selection bias was identified with respect to clinical indications, due to exclusion of these lesions. DW imaging misregistration issues can potentially be avoided in future studies by performing DW imaging earlier during the MR imaging examination, improving patient comfort to reduce motion, and employing alternative pulse sequences or postprocessing techniques to reduce eddy current distortions (45)(46)(47). The low spatial resolution of DW imaging could affect the accuracy of lesion ADC measurements owing to partial volume averaging.…”
Section: Intra-and Interobserver Variabilitymentioning
confidence: 99%
“…It is unclear how this may have affected our study findings; however, no selection bias was identified with respect to clinical indications, due to exclusion of these lesions. DW imaging misregistration issues can potentially be avoided in future studies by performing DW imaging earlier during the MR imaging examination, improving patient comfort to reduce motion, and employing alternative pulse sequences or postprocessing techniques to reduce eddy current distortions (45)(46)(47). The low spatial resolution of DW imaging could affect the accuracy of lesion ADC measurements owing to partial volume averaging.…”
Section: Intra-and Interobserver Variabilitymentioning
confidence: 99%
“…Axial T2-weighted images were also acquired for echo-planar imaging distortion correction. Processing of diffusion-weighted images, including coregistration, correction for eddy currents and subject motion using a 12-mode affine transformation, 21 skull stripping, and normalization to the ICBM-DTI-81 coordinates, 22 was performed using TORTOISE (http://www.nitrc.org/projects/tortoise) 23 and MRI Studio 24 (www. MriStudio.org) software packages.…”
mentioning
confidence: 99%
“…Eddy currents can produce geometric distortions of contraction or dilation, shift and shear in diffusion-weighted images [9,18]. This artifact can be reduced by using a double refocusing SE sequence [19], by image postprocessing [20][21][22] or by using stimulated echo sequences [23]. Another type of artifact generated during diffusion studies is the susceptibility artifact caused by an inhomogeneous magnetic field when an EPI sequence is used to obtain data.…”
Section: Discussionmentioning
confidence: 99%